School environment and practice of accumulated physical activity in young Brazilian students - Mona Gizelle Dreger de Oliveira; Raphael Henrique de Oliveira Araújo; Josiene de Oliveira Couto; Antonio Evaldo dos Santos; Josivan Rosa Santos; Kenia Rejane de Oliveira Batista; Roberto Jerônimo dos Santos Silva (Universidade Federal de Santa Catarina, 2018)
The aim of this study was to verify the association between school environment and accumulated physical activity in Brazilian adolescents. This is a study with secondary data from sample 1, from the third edition of the National School Health Survey, a study carried out with 102.072 children and adolescents enrolled in the ninth school grade. Questions about characteristics of the school environment and the offer of opportunities for physical activity practices were addressed, focusing on information regarding the structure for physical activity and about the regular practice of accumulated physical activities. Variables were organized from the structure of schools and opportunities for the practice of physical activities, while accumulated physical activity was used as the outcome variable. Data were analyzed from a binary logistic regression model, organized in crude and adjusted models, with a significance level of 5%. Data were analyzed from SPSS for Windows, version 22.0. Results indicate that, from the adjustment of variables, there was an association between the practice of accumulated physical activity and the existence of a sports court under conditions of use (OR=1.22, 95%CI=1.18-1.26), or presence of courtyard for use of physical education classes (OR=1.04, 95%CI=1.01-1.06). Association between the offer of varied physical activities, except for physical education classes, and the practice of accumulated physical activity (OR=1.05, 95%CI=1.02-1.08) was identified. Existence of a sports court/courtyard in schools and the offer of extracurricular physical activities are associated with the practice of accumulated physical activity in young Brazilian students.